PENGARUH TERPAAN IKLAN YOUTUBE VERSI "CERITA LOGO" TERHADAP LOYALITAS PELANGGAN BUKALAPAK (Survei Pada followers Akun Instagram @Bukalapak) - Yulio Yakobus (2020)
This study discusses the effect of Youtube ad exposure version of "Logo Strories" towards Bukalapak customer loyalty. The purpose of this study is to determine whether there is an influence of the Youtube ad exposure version of "Logo Strories" towards Bukalapak customer loyalty, and to find out how much influence. The theory used in this research is Elaboration Likelihood Theory. The method used is a quantitative research method. Data collection is done by distributing questionnaires. The population in this study were followers of @Bukalapak Instagram account, for samples using the Lemeshow formula which were then obtained as many as 96 respondents. The sampling technique used in this study is the purposive sampling technique. Data processing in this study uses SPSS version 25 for Windows.Based on the calculation of the coefficient of determination obtained the effect of ad exposure on customer loyalty by 32.1%, while the remaining 67.9% is the influence of other variables not examined in this study. The results of testing the hypothesis using the t test showed that t count 6.646> t table 1.665, it can be concluded that H0 was rejected and Ha was accepted. R value obtained through the correlation test of 0.567 which is in the category of interpretation of the correlation coefficient shows a fairly strong level of influence. So, it can be known and concluded that the Youtube ad exposure version "Logo Stories" has a strong enough influence on the customer loaylty of the Bukalapak on followers of @Bukalapak Instagram account.